2017
DOI: 10.1016/j.lwt.2016.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cooking on apricot texture as a function of cultivar and maturity

Abstract: a b s t r a c tThe rapid loss of fruit firmness is a qualitative decisive factor for characterizing apricot (Prunus armeniaca L.) use (fresh or processed) and commercialization pathways (short or storage). To better understand the texture variability in apricot, we studied the impact of a heat treatment as a function of fruit harvest stage on a large range of cultivars. Eighteen apricot cultivars were characterized at two maturity stages before and after cooking (85 C in light syrup). A compression test allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Apricots after 56 and 70 days storage (NFT and 0–1°C) were selected (Table ). Firmness and texture are important quality attributes for apricot fruit, as they influence consumer acceptability (Ayour et al, ). After the 3 days of shelf life experiment, “Xiaobai” and “Daliguang” apricots stored at 0–1°C showed lower firmness values than those stored at NFT for 56 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apricots after 56 and 70 days storage (NFT and 0–1°C) were selected (Table ). Firmness and texture are important quality attributes for apricot fruit, as they influence consumer acceptability (Ayour et al, ). After the 3 days of shelf life experiment, “Xiaobai” and “Daliguang” apricots stored at 0–1°C showed lower firmness values than those stored at NFT for 56 days.…”
Section: Resultsmentioning
confidence: 99%
“…Apricot ( Prunus armeniaca L.) is a fleshy fruit of commercial and worldwide preferable interest, because of its flavonoids, carotenoids, nutrient contribution from phytochemical constituents such as phenolic compounds, carotenoids, volatiles, and vitamins (Vardi et al, ) and health benefits (Ayour et al, ). The “Xiaobai” apricot and “Daliguang” apricot are major cultivars of the Xinjiang region in China, and are famous for their crisp, juicy texture, and sweet flavor (Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Canned peach samples were additionally tested with a “bulk” firmness test which is designated to evaluate simultaneously the mechanical responses of a number of pieces of specific weight with the employment of a multi‐bladed device (Kramer shear test cell, KST) (Figure 2c). This device is commonly used to analyze the bulk textural features of multiparticle products, such as cereals (Chaunier, Courcoux, Della Valle, & Lourdin, 2005; Kerr, Ward, Mcwatters, & Resurreccion, 2001) and to evaluate the texture of both raw ingredients and finished food products (Ayour et al, 2017; Walter, Truong, & Espinel, 2002), yet with limited exploitation to horticultural commodities (Canet, Alvarez, Luna, & Fernández, 2004; Sousa, Canet, Alvarez, & Fernández, 2007). KST has been employed on some thermally processed commodities, such as pasteurized apricots (Ribas‐Agustí et al, 2017) and diced tomatoes (Rao & Barringer, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been carried out on the textural properties of fruit such as apples, pears, peaches [21][22][23][24][25], but only little information is available on the texture of apricots. Some studies were reported on the impact of cooking on apricot texture [26][27][28][29]. Stanley et al [9] assessed the influence of harvest maturity and cold storage on the firmness, mealiness and gel formation of apricots but only firmness was measured by an instrument, as mealiness and gel formation were determined by trained assessors.…”
Section: Introductionmentioning
confidence: 99%